2020
DOI: 10.1159/000505148
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Ejection Fraction Recovery in Patients with Heart Failure and Reduced Ejection Fraction Treated with Sacubitril/Valsartan

Abstract: Background: A significant number of heart failure (HF) patients with reduced left ventricular ejection fraction (LVEF) experience ventricular function recovery during follow-up. We studied the variables associated with LVEF recovery in patients treated with sacubitril/valsartan (SV) in clinical practice. Methods: We analyzed data from a prospective and multicenter registry including 249 HF outpatients with reduced LVEF who started SV between October 2016 and March 2017. The patients were classified into 2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…Patients who were younger than 18 years, those who had combined significant valvular heart disease, or those who had undergone cardiac resynchronization therapy were excluded. Responders to HF medication were defined as patients with an increase in LVEF from ≥10% to a final value of ≥35% according to previous studies [ 10 , 15 ]. The present study was carried out according to the principles of the Declaration of Helsinki and was approved by the Clinical Research Institute of Mediplex Sejong Hospital (approved on 9 June 2020; IRB No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were younger than 18 years, those who had combined significant valvular heart disease, or those who had undergone cardiac resynchronization therapy were excluded. Responders to HF medication were defined as patients with an increase in LVEF from ≥10% to a final value of ≥35% according to previous studies [ 10 , 15 ]. The present study was carried out according to the principles of the Declaration of Helsinki and was approved by the Clinical Research Institute of Mediplex Sejong Hospital (approved on 9 June 2020; IRB No.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, new agents acting on the renin-angiotensin-aldosterone and neutral endopeptidase systems have demonstrated greater improvement in functional class and reduction in cardiac mortality compared with that seen the angiotensin-converting enzyme inhibitor (ACEI), enalapril, in patients with HFrEF [ 6 ]. The subgroup analysis in the PARADIGM-HF study and several other studies have suggested that sacubitril/valsartan improves left ventricular (LV) function and reduces hospitalization and cardiac mortality rates [ 7 , 8 , 9 , 10 , 11 ]. However, most of the subsequent studies on LV function had short follow-up duration or were single-arm studies.…”
Section: Introductionmentioning
confidence: 99%
“…Sacubitril/valsartan improves LVEF and significantly reduces emergency treatment rate in patients with HFrEF. [ 24 ] Patients who received a higher initial dose of sacubitril/valsartan tended to have a better recovery of left ventricular function. In patients whose left ventricular function has recovered, a gradual decrease in the dose of sacubitril/valsartan is associated with deterioration of restored cardiac function.…”
Section: What Was Found In Previous Researchmentioning
confidence: 99%
“…The study by Díez-Villanueva et al [4] adds to the knowledge base regarding associations between ARNI therapy and cardiac remodeling. This study included 249 outpatients with HF and reduced LVEF who started sacubitril-valsartan between October 2016 and March 2017.…”
mentioning
confidence: 98%
“…The results of Díez-Villanueva et al [4] suggest that the reverse myocardial remodeling benefit of sacubitrilvalsartan happens in the early beginning of the treatment. DOI: 10.1159/000506538…”
mentioning
confidence: 99%